Neurovascular disease in Switzerland: 10‐year trends show non‐traditional risk factors on the rise and higher exposure in women. (22nd June 2022) - Hänsel, Martin; Steigmiller, Klaus; Luft, Andreas R.; Gebhard, Catherine; Held, Ulrike; Wegener, Susanne
Abstract: Background and purpose: Effective risk factor modification is the prerequisite to prevent neurovascular disease such as stroke or vascular dementia. Non‐traditional vascular risk factors (nt‐vrfs) including stress significantly add to the risk of neurovascular disease arising from traditional vascular risk factors (t‐vrfs). In order to discover sex‐specific changes that may underlie previously reported inclines in the prevalence of neurovascular and cardiovascular disease in women, 10‐year trends in the prevalence of vrfs in Switzerland were assessed. Methods: Anonymized data from 22, 134 participants (51% women) of the governmental Swiss Health Survey, performed every 5 years (2007, 2012 and 2017), were obtained. Epidemiological parameters, t‐vrfs and nt‐vrfs were analyzed in a cross‐sectional study design. Results: Over the observation period, the number of women having full‐time jobs increased considerably (2007 38%, 2012 39%, 2017 44%). This was accompanied by a substantial rise in the prevalence of nt‐vrfs in women and men including stress at work (2007, not available; 2012 women/men 58%/60%; 2017 women/men 66%/65%), low locus of control (women/men: 2007 21%/19%, 2012 22%/19%, 2017 25%/22%) and sleep disorders (women/men: 2007 30%/22%, 2012 28%/20%, 2017 32%/26%). Amongst t‐vrfs, only the prevalence of obesity and hypercholesterolemia increased over time in both sexes, whilst other t‐vrfs remained stable (hypertension [27%], diabetes [5%]) or decreased (smoking [9.4 cigarettes/day]). Conclusions: A rise in women's economic participation alongside a higher affection with nt‐vrfs in the female Swiss population emphasizes the need to improve vascular risk stratification and implement effective preventive measures for neurovascular and cardiovascular disease. Abstract : Vascular risk factors increase the likelihood of stroke and neurovascular disease. Non‐traditional risk factors, including stress, significantly add to this risk. Using data from the Swiss Healthy Survey 2007–2017, we show that non‐traditional risk factors are on the rise, particularly in women. We need effective preventive measures for neuro‐ and cardiovascular disease, that apply to women and men alike.